2016
DOI: 10.1016/j.gdata.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptome expression analysis and comparison of two different strains of Plasmodium falciparum using RNA-Seq

Abstract: The emergence and distribution of drug resistance in malaria are serious public health concerns in tropical and subtropical regions of the world. However, the molecular mechanism of drug resistance remains unclear. In the present study, we performed a high-throughput RNA-Seq to identify and characterize the differentially expressed genes between the chloroquine (CQ) sensitive (3D7) and resistant (Dd2) strains of Plasmodium falciparum. The parasite cells were cultured in the presence and absence of CQ by in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Our comprehensive results indicate that halofuginone damages biological pathways and induces autophagy in E. tenella. Previous studies also found that differential expression of regulated genes may lead to differences in drug-resistant and drug-sensitive strains (Antony et al, 2016;Ingham et al, 2020;Xie et al, 2020;Laing et al, 2022;Okombo et al, 2022;Zhang et al, 2022). Hence, it was expected that long-term selection would lead to transcriptional changes in different genes in the resistant strain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our comprehensive results indicate that halofuginone damages biological pathways and induces autophagy in E. tenella. Previous studies also found that differential expression of regulated genes may lead to differences in drug-resistant and drug-sensitive strains (Antony et al, 2016;Ingham et al, 2020;Xie et al, 2020;Laing et al, 2022;Okombo et al, 2022;Zhang et al, 2022). Hence, it was expected that long-term selection would lead to transcriptional changes in different genes in the resistant strain.…”
Section: Discussionmentioning
confidence: 97%
“…To evade different drug pressures, Eimeria drug-resistant strains may depend on different mechanisms of gene regulation (Xie et al, 2020). Previous studies have suggested that the differential expression of regulated genes may lead to differences in drug-resistant and drug-sensitive strains, and the current series of studies using transcriptome analysis has been successful in dissecting drug resistance mechanisms (Antony et al, 2016;Ingham et al, 2018Ingham et al, , 2020Xie et al, 2020;Zhang et al, 2022). Here, we performed transcriptome analysis to explore the mechanism of halofuginone resistance in E. tenella.…”
Section: Introductionmentioning
confidence: 98%
“…Data collection. Raw sequence data from a laboratory-adapted sensitive and resistant strain of Plasmodium falciparum were obtained from the NCBI SRA and deposited in the NCBI Bio project database under the accession number PRJNA308455 [12]. The raw sequence data of Plasmodium vivax sensitive and resistant strains are stored in the NCBI SRA under the accession numbers SRR14191963 and SRR332573.…”
Section: Methodsmentioning
confidence: 99%
“…Sporozoites migrate to the mosquito's salivary glands after 10-18 days. When an Anopheles mosquito sucks blood from another human, the sporozoites are injected with anticoagulant saliva and migrate to the liver, starting a new cycle [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. As a result, the infected mosquito acts as a "vector" for the disease, while infected humans transmit the parasite to the mosquito.…”
Section: Introductionmentioning
confidence: 99%